The cyclin-dependent kinase inhibitor p27 kip1 regulates radial stem cell quiescence and neurogenesis in the adult hippocampus - Andreu, Zoraida; Khan, Muhammad Amir; Gonzalez-Gomez, Pilar; Negueruela, Santiago; Hortigueela, Rafael; Emeterio, Juana San; Ferron, Sacri R.; Martinez, Gloria; Vidal, Anxo; Farinas, Isabel; Lie, Dieter Chichung; Mira, Helena (Stem Cells, 2015)
Members of the cyclin-dependent kinase (CDK)-inhibitory protein (CIP)/kinase-inhibitory protein (KIP) family of cyclin-dependent kinase inhibitors regulate proliferation and cell cycle exit of mammalian cells. In the adult brain, the CIP/KIP protein p27(kip1) has been related to the regulation of intermediate progenitor cells located in neurogenic niches. Here, we uncover a novel function of p27(kip1) in the adult hippocampus as a dual regulator of stem cell quiescence and of cell-cycle exit of immature neurons. In vivo, p27(kip1) is detected in radial stem cells expressing SOX2 and in newborn neurons of the dentate gyrus. In vitro, the Cdkn1b gene encoding p27(kip1) is transcriptionally upregulated by quiescence signals such as BMP4. The nuclear accumulation of p27(kip1) protein in adult hippocampal stem cells encompasses the BMP4-induced quiescent state and its overexpression is able to block proliferation. p27(kip1) is also expressed in immature neurons upon differentiation of adult hippocampal stem cell cultures. Loss of p27(kip1) leads to an increase in proliferation and neurogenesis in the adult dentate gyrus, which results from both a decrease in the percentage of radial stem cells that are quiescent and a delay in cell cycle exit of immature neurons. Analysis of animals carrying a disruption in the cyclin-CDK interaction domain of p27(kip1) indicates that the CDK inhibitory function of the protein is necessary to control the activity of radial stem cells. Thus, we report that p27(kip1) acts as a central player of the molecular program that keeps adult hippocampal stem cells out of the cell cycle.
EVALuna2:26326